Provisional Agenda for the Twenty-Third Meeting of the International Monetary and Financial Committee. (Policy Papers; Policy Paper ;, 2011)
A joint meeting of IMFC and G-20 Members will be held on Friday, April 15 on The Governance of Multilateral Surveillance from 7:00 pagesm. until 8:30 pagesm. in HQ1 Meeting Halls A and B.